Effects of a Targeted Multimodal Exercise Program Incorporating High‐Speed Power Training on Falls and Fracture Risk Factors in Older Adults: A Community‐Based Randomized Controlled Trial. (January 2014) - Gianoudis, Jenny; Bailey, Christine A; Ebeling, Peter R; Nowson, Caryl A; Sanders, Kerrie M; Hill, Keith; Daly, Robin M
ABSTRACT Multimodal exercise programs incorporating traditional progressive resistance training (PRT), weight‐bearing impact training and/or balance training are recommended to reduce risk factors for falls and fracture. However, muscle power, or the ability to produce force rapidly, has emerged as a more crucial variable to functional decline than muscle strength or mass. The aim of this 12‐month community‐based randomized controlled trial, termed Osteo‐cise: Strong Bones for Life, was to evaluate the effectiveness and feasibility of a multimodal exercise program incorporating high‐velocity (HV)‐PRT, combined with an osteoporosis education and behavioral change program, on bone mineral density (BMD), body composition, muscle strength and functional muscle performance in older adults. Falls incidence was evaluated as a secondary outcome. A total of 162 older adults (mean ± SD; 67 ± 6 years) with risk factors for falls and/or low BMD were randomized to the Osteo‐cise program (n = 81) or a control group (n = 81). Exercise consisted of fitness center‐based HV‐PRT, weight‐bearing impact and challenging balance/mobility activities performed three times weekly. After 12 months, the Osteo‐cise program led to modest but significant net gains in femoral neck and lumbar spine BMD (1.0% to 1.1%, p < 0.05), muscle strength (10% to 13%, p < 0.05), functional muscle power (Timed Stair Climb, 5%, p < 0.05) and dynamic balance (Four Square Step Test 6%, p < 0.01; Sit‐to‐Stand, 16%, p < 0.001) relative to controls. There was no effect on total body lean mass or mobility (timed‐up‐and‐go), and no difference in falls rate (incidence rate ratio [IRR], 1.22; 95% confidence interval [CI], 0.72–2.04). In conclusion, this study demonstrates that the Osteo‐cise: Strong Bones for Life community‐based, multimodal exercise program represents an effective approach to improve multiple musculoskeletal and functional performance measures in older adults with risk factors for falls and/or low BMD. Although this did not translate into a reduction in the rate of falls, further large‐scale trials are needed to evaluate the efficacy of this multimodal approach on reducing falls and fracture. © 2014 American Society for Bone and Mineral Research.